Non-farm enterprises: Strengthening youth resilience in 18 rural districts of Zimbabwe - Tirivanhu, Doreen; Chevo, Tafadzwa; Mapangisana, Toga (University of Zimbabwe, 2023)
Smallholder communities are faced with shocks and stresses caused by the effects of climate change and variability, as well as socioeconomic characteristics threatening their communities, which rely on rainfed crop and livestock production. This has a negative effect on young people, who are still innovative and energetic to take part in different initiatives to improve their livelihoods. This study uses a qualitative data analysis to evaluate youth participation in nonfarm activities among smallholder communities of Zimbabwe. The data was obtained from the ZRBF OMS surveys conducted from 2017 to 2019. The results show that youths participate mainly in nontimber forest products, natural resource management, water infrastructure development, DRM/ DRR training, welding, cross-border trading, sewing, and village savings and loans groups, which were important for their adaptive, absorptive, and transformative capacities. The productivity of youth’s nonfarm enterprises was affected by the stability of local currency, capacity building, access to markets, load shedding, and the COVID-19 pandemic. Based on these results, there is need for continued support of the youths by providing them with a conducive environment to showcase their skills, and improve their access to information and training, to improve co-learning and co-innovation for adaptation, absorption and transformation among communities.